Verbal And Phonetic Paraphasias In The Case Of Expressive Aphasia (broca’s Aphasia) Patients: Study Of Five Cases - Faizah Saleh, Al-hammadi (Université de M'sila, 2018)
Abstract: Aphasia also known as Broca’s aphasia is a neurological disorder that causes a loss of communication skills. This study was undertaken to investigate the nature of verbal and phonetic transformations among patients suffering from Broca’s aphasia. The nature of the verbal transformations produced by Broca's aphasia involves replacement, deletion, and distortion. The hypotheses of the study were as follows: Replacement is among the most frequently-used verbal transformations among Broca's aphasia, and to determine whether Verbal manifestations are identical in all cases. The study used a descriptive approach based on the case study methodology. The study is crucial insofar as it highlights the manifestations of verbal paraphasias among patients with Broca’s Aphasia, and determines the predominance of verbal paraphasias among patients with Broca's Aphasia. The sample consisted of five cases that were selected in an intentional manner. The demonstration of the study hypothesis indicates the validity of the assumptions on which it was based. الملخص: إن فقدان القدرة على الكلام المعروف باسم حبسة بروكا هو اضطراب عصبي يسبب فقدان مهارات الاتصال. وقد أجريت هذه الدراسة للتحقيق في طبيعة التحولات اللفظية والصوتية بين المرضى الذين يعانون من حبسة بروكا وطبيعة التحولات اللفظية التي تنتجها حبسة بروكا تتمثل في الابدال، الحذف، والتشويه. وتمثلت فرضيات الدراسة فيما يلي: هل الابدال هو من بين التحولات اللفظية الأكثر استخداما عند حبسي بروكا؟ وهل كانت المظاهر اللفظية متطابقة في جميع الحالات؟ استخدمت الدراسة المنهج الوصفي القائم على منهج دراسة الحالة. الدراسة بقدر ما تسلط الضوء على مظاهر التحول اللفظي بين المرضى الذين يعانون من حبسة بروكا، ويحدد هيمنة الابدال بين المرضى الذين يعانون من حبسة بروكا. وتكونت العينة من خمس حالات تم اختيارها بطريقة قصدية. ويدل تحقق فرضية الدراسة على صحة التصورات النظرية التي قامت عليها الكلمات المفتاحية: التحولات الشفوية – الابدال –حبسة بروكا.
Keywords: التحولات الشفوية – الابدال –حبسة بروكا. verbal paraphasias, substitution, Broca’s aphasia.